Simulation of partial discharges under influence of impulse voltage - Trotsenko, Yevgeniy; Brzhezitsky, Volodymyr; Protsenko, Olexandr; Chumack, Vadim; Haran, Yaroslav (Technology audit and production reserves, 2017)
The object of research is an equivalent circuit for a dielectric with a weakened insulation (for example, with a gas cavity) with a partial discharge. The test with partial discharge measurement by application of alternating voltage is one of the main methods of diagnostics and non-destructive tests. According to GOST 1516.2, the application of impulse test voltage does not necessarily end with a breakdown of the electrical equipment insulation or the absence of breakdown. There may be a partial breakdown of insulation, in which not all insulation of electrical equipment will be damaged, but only some of its part. It is quite difficult to detect such damage in accordance with GOST 1516.2, but registration of partial discharges will allow this to be detected by increasing their intensity. The use of existing technical means for measuring the characteristics of partial discharges at alternating voltage is not acceptable for the task in question. Therefore, it is preliminary necessary to carry out computer simulation of partial discharges when the impulse voltage is applied. A circuit simulation model of a dielectric with a gas cavity with partial discharge has been created. It is shown how, by means of a combination of various elements, to simulate the breakdown of a gas cavity. The operability of the model under the influence of alternating voltage is checked. It is confirmed that voltage harmonic distortions lead to an increase in the number of partial discharges. A study of the model is carried out when it is subjected to a full lightning voltage impulse. As a result, it has been established that partial discharges occur in the gas cavity both at the impulse front and at its tail. Diagnosis of the insulation condition using the measurement of the partial discharge characteristics under the influence of impulse voltage will be more informative. In particular, it will allow to detect partial breakdowns of insulation that occur during impulse tests and are absent in standard tests with application of alternating voltage. To carry out such measurements it is necessary to develop new techniques, equipment and diagnostic procedures.